Dinamika Pisang (Filipina-Sangihe) Di Perbatasan Indonesia-Filipina - Pristiwanto Pristiwanto (Antropologi Indonesia, 2016)
Indonesia citizens, who are resident in the southern Philippines is estimated at 8,000 inhabitants. They are commonly known as Pisang, an abbreviation of the Philippines-Sangihe or residents who have “blood ties” with Sangihe (Indonesia) which then had settled in the Philippines. In fact, their Philippine area residence does not become a barrier for the Pisang to remain in a relationship of kinship with the Indonesian Sangihe, through cross-border activity. This reality makes the issue of mobility become important because they do activities on the territory of two nation-states. The Pisang do trade, family visits and political activities even activities that indicated as transnational crime in border area. Ironically, studies that literally uplift the phenomenon of Pisang has not been found. Based on field research, this article describes the dynamics and controversy of Pisang activities in Indonesia sea-border area, the Sangihe Archipelago Regency.Keywords: Indonesia, Philipine, Pisang, Border Area.